Assessing Drinking Water Accessibility in Diverse Provinces of Nepal - Limbu, Lila Prasad (Humanities and Social Sciences Journal, 2024)
Access to safe and reliable drinking water remains a critical concern in Nepal, where geographical, socioeconomic, and infrastructural disparities shape drinking water security across regions. This study aims to identify provincial differences in drinking water access and to examine the disparities between rural and urban areas. Using a mixed-methods approach, it integrates quantitative data from the 2022 Nepal Demographic and Health Survey (NDHS) with qualitative insights from observation and key informant interviews. The quantitative sample includes 3,997 households from both urban and rural areas, analyzed through chi-square tests and cross-tabulations to assess variations in availability and accessibility. The findings reveal significant provincial and regional disparities: urban households have greater access to on-premises drinking water, while rural areas—particularly in Karnali and Sudurpaschim Provinces—experience limited, unreliable, and often unsafe drinking water sources. Qualitative evidence further highlights poor enforcement of national drinking water quality standards and inadequate regulatory oversight. The study concludes that although access has improved in some regions, inequalities in quality and sustainability continue. It recommends more vigorous policy enforcement, decentralized infrastructure investment, and community-based education on drinking water safety. Coordinated action among government bodies and stakeholders is essential to ensure equitable, sustainable, and safe access to drinking water throughout Nepal.